The Relationship Between Cognitive Abilities and the Decision-Making Process: The Moderating Role of Self-Relevance - Jin, Menghan; Ji, Lingling; Peng, Huamao (Frontiers in Psychology, 2019)
This study aimed to investigate the relationship between cognitive abilities and age differences in information search and the moderating role of task self-relevance by measuring the decision-making process of participants in both high and low self-relevance decision tasks. The participants were 57 young adults and 65 older adults who viewed five alternatives ☓ five attributes decision matrices in which they needed to open the information cells they wanted to explore by clicking the mouse. Processing speed, verbal fluency, working memory and vocabulary were measured as cognitive abilities. The dependent variables were search engagement (including time-related engagement and frequency-related engagement) and search pattern (calculated based on alternative-based or attribute-based search). Results from a structured equation model showed that age negatively predicted these cognitive abilities (processing speed, verbal fluency, working memory and vocabulary), and positively predicted information searching engagement. Processing speed mediated the impact of age on study time per cell under tasks with both high and low self-relevance; whereas verbal fluency mediates total searching time and searching time per check only when the task is highly self-related, but not in the task with low self-relevance. These results suggested that self-relevance could moderate the mediation effect of verbal fluency on the relationship between age and information searching time, which means that older adults whose verbal fluency was limited need relatively more time to search information to make an informed decision. However, this impact is only sufficient when the decision task is highly self-related and draws more engagement motivation into it.